Fluid flow generates bacterial conjugation hot spots by increasing the rate of shear-driven cell–cell encounters - Matti Zbinden; Jana S. Huisman; Natasha Blitvic; Roman Stocker; Jonasz Słomka (Proceedings of the National Academy of Sciences, 2025)
Conjugation accelerates bacterial evolution by enabling bacteria to acquire genes horizontally from their neighbors. Plasmid donors must physically encounter and connect with recipients to allow plasmid transfer, and different environments are characterized by vastly different encounter rates between cells, based on mechanisms ranging from simple diffusion to fluid flow. However, how the environment affects the conjugation rate by setting the encounter rate has been largely neglected, mostly because existing experimental setups do not allow for direct control over cell encounters. Here, we describe the results of conjugation experiments in Escherichia coli in which we systematically varied the magnitude of shear flow using a cone-and-plate rheometer to control the encounter rate. We found that the conjugation rate increases with shear until it peaks at an optimal shear rate ( γ ˙ = 1 × 10 2 s − 1 ), reaching a conjugation rate fivefold higher than the baseline set by diffusion-driven encounters. This optimum marks the transition from a regime in which shear promotes conjugation by increasing the rate of cell–cell encounters to a regime in which shear disrupts conjugation. Regions of high fluid shear are widespread in aquatic systems, in the gut of host organisms, and in soil, and our results indicate that these regions could be hot spots of bacterial conjugation in the environment.